Suppression of total harmonic distortion using single-phase shunt active power filter with fuzzy logic controller - Usman, Hamisu (2013)
In the previous years, electrical power system equipment and devices were designed to produce purely sinusoidal voltage and current wave forms. But nowadays, with much interest and wide spreads of power electronics equipment and devices utilized for industrial, commercials and residential consumers, these equipment and other electronics devices can no longer operate with an ideal current and voltage waveform,because of the non-linearity of the equipment and devices in nature, that draw harmonics currents and voltages from the supply. With this, traditional LC passive filters were first introduced to mitigate harmonics currents/voltages and reactive power produced by non-linear loads. But passive filters are limited in operation due to its limitations such as heavy in sizes, bulky and a tendency for parallel and series resonances with supply impedance. Due to the limitations of passive filters, active power filters are now the dynamic and viable solution to suppress current harmonics and reactive power drawn by non-linear loads. In this thesis, the modeling and simulation of single-phase shunt active power filter to mitigate the unwanted harmonics currents/voltages and reactive power drawn by non-linear loads are proposed. Fuzzy logic controller (FLC) was used to control the active filter, because of its simplicity and does not require any accurate mathematical model. Simulations arecarried out in MATLAB/SIMULINK and SIMPOWER tool box environment. In the simulation, synchronous reference frame was used to extract the harmonic reference current produced by the non-linear loads. The simulation results were validated with the experimental results of the hardware proto- type in the laboratory. Digital signal processor DSP TMS320F28335 was used in order to demonstrate the feasibility and good performance of the proposed control algorithm. The total harmonics distortions (THD %) for the simulation results are within the IEEE 519-1992 harmonic standard. While the experimental results does not comply with the recommended IEEE 519-1992 harmonic standard limits because of the real time hardware implementation and losses within the real time components.